The Effects of Reconditioning Exercises Following Prolonged Bed Rest on Lumbopelvic Muscle Volume and Accumulation of Paraspinal Muscle Fat - De Martino, Enrico; Hides, Julie; Elliott, James M.; Hoggarth, Mark A.; Zange, Jochen; Lindsay, Kirsty; Debuse, Dorothée; Winnard, Andrew; Beard, David; Cook, Jonathan A.; Salomoni, Sauro E.; Weber, Tobias; et al. (Frontiers in Physiology, 2022)
Reduced muscle size and accumulation of paraspinal muscle fat content (PFC) have been reported in lumbopelvic muscles after spaceflights and head-down tilt (HDT) bed rest. While some information is available regarding reconditioning programs on muscle atrophy recovery, the effects on the accumulation of PFC are unknown. Recently, a device (the Functional Re-adaptive Exercise Device—FRED) has been developed which aims to specifically recruit lumbopelvic muscles. This study aimed to investigate the effects of a standard reconditioning (SR) program and SR program supplemented by FRED (SR + FRED) on the recovery of the lumbopelvic muscles following 60-day HDT bed rest. Twenty-four healthy participants arrived at the facility for baseline data collection (BDC) before the bed rest period. They remained in the facility for 13-day post-HDT bed rest and were randomly allocated to one of two reconditioning programs: SR or SR + FRED. Muscle volumes of the lumbar multifidus (LM), lumbar erector spinae (LES), quadratus lumborum (QL), and psoas major (PM) muscles were measured from axial T1-weighted magnetic resonance imaging (MRI) at all lumbar intervertebral disc levels. PFC was determined using a chemical shift-based lipid/water Dixon sequence. Each lumbopelvic muscle was segmented into four equal quartiles (from medial to lateral). MRI of the lumbopelvic region was conducted at BDC, Day-59 of bed rest (HDT59), and Day-13 after reconditioning (R13). Comparing R13 with BDC, the volumes of the LM muscle at L4/L5 and L5/S1, LES at L1/L2, and QL at L3/L4 had not recovered (all—p < 0.05), and the PM muscle remained larger at L1/L2 (p = 0.001). Accumulation of PFC in the LM muscle at the L4/L5 and L5/S1 levels remained higher in the centro-medial regions at R13 than BDC (all—p < 0.05). There was no difference between the two reconditioning programs. A 2-week reconditioning program was insufficient to fully restore all volumes of lumbopelvic muscles and reverse the accumulation of PFC in the muscles measured to BDC values, particularly in the LM muscle at the lower lumbar levels. These findings suggest that more extended reconditioning programs or alternative exercises may be necessary to fully restore the size and properties of the lumbopelvic muscles after prolonged bed rest.